Modelo predictivo del desempeño eléctrico en función de la geometría de trazas de cobre con pestañas en circuitos impresos. - Solís-López, Brenda (Instituto Tecnológico de Costa Rica, 2018)
The increase in data rates and the constant size reduction of digital systems, has exposed the shortcomings in structures that operate above the GHz range. A common problem is the appearance of noise due to electromagnetic coupling between nearby lines. It has been shown that one of the ways to deal with this problem, is to add copper tabs to the traces, thus becoming analytical material. However, an accurate study of the behavior of these structures implies large computational resources and extensive simulation times. Knowing this problem, it is intended to reach mathematical expressions that manage to model the behavior of these complex traces, without the need for resource intensive simulations. To achieve this, a series of full-wave simulations are developed to create and validate the predictive models.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2018.
Keywords: Simulación; Ondas; FEXT; Crosstalk; Tabs; Parámetros; Integridad; Señales; Modelos; Superficies; Diseño; Experimentos; Research Subject Categories::TECHNOLOGY::Electrical engineering, electronics and photonics::Electronics